Development pathways and land management in Uganda - Pender, John L.; Jagger, Pamela; Nkonya, Ephraim M.; Sserunkuuma, Dick (Elsevier, 2004)
This paper investigates the patterns and determinants of change in income strategies ("development pathways"), land management, resource and human welfare conditions in Uganda since 1990, based upon a community-level survey conducted in 107 villages. Six dominant development pathways were found, all but one of which involved increasing specialization in already dominant activities. Of these, expansion of banana and coffee production was most associated with adoption of resource-conserving practices and improvements in resource conditions and welfare. The influence of other factors on rural development––including population pressure, road and market development, irrigation, and presence of programs and organizations––is also investigated.